PENERAPAN TEKNOLOGI KARANTINA: UPAYA MEMBUKA PELUANG EKSPOR BUAH-BUAHAN INDONESIA - Rokhani Hasbullah (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT Export of Indonesian fruit are constrained by very tight quarantine regulations, because some  produces are host for Tephritidae  fruit flies that are considered a quarantine risk by many importing countries. To be accepted by importing markets, the produces must be treated to ensure that they are free of the fruit flies. Since the prohibition of chemical method for insect disinfestation process (like ethylene dibromide, EDB) in 1984, a new method by means of heat treatment was developed as a quarantine technology This method has been applied in several fruit exporting countries such as: Australia, the Philippines, Taiwan and Thailand. Heat treatment in postharvest handling is a method of heating fruit to kill insects eggs and larvae of fruit flies prior to fresh market shipment without damaging the produces There are many factors influence the heat on postharvest fruit quality such as cultivar,  fruit size, morphological characteristics, stage of ripeness. and treatment method. Therefore, the applicability of this technology should be assessed on fruit by fruit basis in pursuing the objective of killing the pests/diseases without adversely affecting the  market quality of the fruit. Diterima:12 Pebruari  2007, Disetujui:. 27 Maret 2007